RICKETIS IN CHILDREN: CAUSES, CLINICAL PICTURE, DIAGNOSIS, TREATMENT - Ibatova Sh. M.; Mamatkulova D. Kh. (American Journals Publishing, 2024)
Rickets occurs during a period of intensive growth and development of the child. The main cause of rickets in children is a lack of vitamin D. Diagnosis of rickets is based on anamnesis, clinical picture of the disease, and biochemical blood tests. To assess skeletal deformities, X-rays of long bones are taken. Computed tomography and densitometry provide a more accurate assessment of the condition of bone tissue. Treatment of vitamin rickets should be comprehensive, long-term and aimed both at eliminating the causes that caused it and at eliminating hypovitaminosis D.
Keywords: Rickets, children, clinic, diagnosis, treatment, prevention.